Assessment of alkali aggregate reaction avoidance measures and alkali aggregate reaction tests worldwide - Mwatile, Martha Ndinelao (Department of Civil Engineering, 2021)
Alkali Aggregate Reaction (AAR) is a deterioration mechanism which affects concrete structures all over the world. Different parts of the world employ various mitigation and control measures for AAR damage. Different tests are also performed worldwide to assess AAR. With the variety of AAR avoidance measures and AAR tests performed worldwide, it is necessary to have a thorough compilation and critical assessment of these AAR avoidance measures and AAR tests, which may be of assistance to engineers and other professionals who are involved in structural and material design of concrete structures or in the construction, quality control and condition monitoring and assessment of concrete structures. This dissertation aims to outline the types of AAR and the mechanisms associated with them, and to highlight case studies of AAR incidences around the world. This dissertation further aims to provide a comprehensive compilation and analysis of various AAR avoidance measures as well as AAR tests that are performed worldwide. Commonalities and differences will be highlighted between the different case studies, and critical analyses will be done on the AAR avoidance measures and AAR tests that will be discussed. There are three main types of AAR, distinguishable by the aggregate source. These are: AlkaliSilica Reaction (ASR), Alkali-Silicate Reaction and Alkali-Carbonate Rock Reaction (ACR). Since AAR is a type of internal chemical damage to concrete, it can be avoided by engineering design and by carefully selecting the concrete construction materials. In order for damaging AAR to occur in concrete, the following conditions need to be met: • Reactive silica in the aggregates should be present • Alkali, which is primarily from Portland cement, should be of a sufficient concentration • There should be sufficient moisture in the concrete • Portlandite should be in a sufficient concentration (this is specifically for ACR) To prevent the occurrence of AAR in concrete, one or more of the conditions above should be eliminated, except for the case of ASR in which one or more of the first three conditions should be eliminated. Since this dissertation mainly focuses on ASR, only the first three conditions will be considered as these are the only conditions for the occurrence of ASR. Various testing methods are employed all over the world to assess AAR. These tests include tests performed to assess whether certain aggregates are susceptible to AAR; tests to assess the performance of specific concrete mixes and thus determine if they are susceptible to AAR, and also tests performed to assess the occurrence and extent of AAR in existing concrete structures.